Investigating the effect of betamethasone loaded lipid-polymer hybrid nanoparticles for autoimmune diseases - Su, Isabella Jing Tian (2016)
Presently, the use of nanoparticles (NP) to encapsulate and deliver drugs for treatment of autoimmune diseases such as psoriasis and rheumatoid arthritis focus on targeting macrophages to reduce inflammatory response. Tumor necrosis factor alpha (TNF-α) is expressed by macrophages during inflammation and can be used to evaluate the effectiveness of inflammatory drug therapies in reducing TNF-α expression. Betamethasone 17-valerate (B17V) is a corticosteroid commonly used in anti-inflammatory drug formulations to suppress inflammation and the immune system. Using a modified nanoprecipitation method, lipid-polymer hybrid nanoparticles (LPN) were synthesized at 20% wt/wt lipid/polymer mass ratio and 7:3 lipid/lipid-PEG molar ratio. Characterization by dynamic light scattering (DLS) and high performance liquid chromatography (HPLC) identified the optimal drug loaded to be 20% wt/wt. Stability tests were carried out over 120hrs and BLPNs were evaluated to be stable with no significant change in size and polydispersity index over the time period. In vitro treatment of free drug and betamethasone LPN (BLPN) on macrophages showed significant reduction of TNF-α expression from 54.32 pg/ml to 16.95±2.82pg/ml and 20.66±1.63pg/ml respectively, suggesting that BLPNs may be useful as a drug delivery system to reduce inflammatory responses in autoimmune diseases. Treatment with free B17V or B17V-loaded nanoparticles did not show any significant cytotoxicity on the tested monocytes and macrophages.